PRINSIP UMUM DAN KHUSUS PENGEMBANGAN KURIKULUM: (IMPLIKASINYA TERHADAP PENERAPAN KURIKULUM 2013) - Niswa (LPPM STAI DARUSSALAM LAMPUNG, 2019)
This article aims to describe the general and specific principles of curriculum development and to analyze the impact of the 2013 curriculum. The method used in this paper is to use the literature method (Librabry Research). The educational curriculum is always changing or developing, this is a form of response to the progress and demands of the times. However, curriculum change and development is certainly based on the principles that form the basis of development for educational curricula. The principles to be put forward include the principles in curriculum development, both in general and specifically. The results of this study indicate that, general principles in curriculum development include goal-oriented principles, competence, relevance, efficiency, effectiveness, flexibility, integrity, continuity, synchronization, objectivity and democracy. Specific principles include the principles of objectives, content, media, learning resources and evaluation. The expected positive impact of this article is that curriculum developers should pay particular attention to general and specific principles in curriculum development so that the objectives of the curriculum can be maximally achieved.